Helminths: Immunoregulation and Inflammatory Diseases—Which Side Are Trichinella spp. and Toxocara spp. on? - Carmen Aranzamendi; Ljiljana Sofronic-Milosavljevic; Elena Pinelli (Journal of Parasitology Research)
Macropathogens, such as multicellular helminths, are considered masters of immunoregulation due to their ability to escape host defense and establish chronic infections. Molecular crosstalk between the host and the parasite starts immediately after their encounter, which influences the course and development of both the innate and adaptive arms of the immune response. Helminths can modulate dendritic cells (DCs) function and induce immunosuppression which is mediated by a regulatory network that includes regulatory T (Treg) cells, regulatory B (Breg) cells, and alternatively activated macrophages (AAMs). In this way, helminths suppress and control both parasite-specific and unrelated immunopathology in the host such as Th1-mediated autoimmune and Th2-mediated allergic diseases. However, certain helminths favour the development or exacerbation of allergic responses. In this paper, the cell types that play an essential role in helminth-induced immunoregulation, the consequences for inflammatory diseases, and the contrasting effects of Toxocara and Trichinella infection on allergic manifestations are discussed.